Study on Hydrogen Gas concentration to Voltage and Resistance using Semiconductor Hydrogen Gas Sensor - Ahmad Arif Hasibuan; Elin Yusibani; M Syukri Surbakti (PSI-Aceh, 2016)
Study on hydrogen gas concentration to changes in voltage and resistance using semiconductor hydrogen gas sensor has been done. The system which has been designed will measure any changes in the voltage and resistance of the sensor automatically when the sensor is given a variation of concentration on hydrogen gas. On the condition of gas with low concentration, the sensor output voltage obtained worth 0:08 Volt and the sensor resistance value of 180 KΩ. On the increase in gas concentration causes an increase in sensor output voltage and a decrease in the value of resistanceStudi tentang pengaruh konsentrasi kadar gas hidrogen terhadap perubahan tegangan dan resistansi menggunakan sensor gas hidrogen berbasis semikonduktor telah berhasil dilakukan. Sistem yang telah dirancang akan mengukur setiap perubahan tegangan dan resistansi secara digital pada sensor saat diberikan variasi terhadap konsentrasi kadar gas hidrogen. Pada kondisi gas dengan konsentrasi rendah diperoleh tegangan output sensor senilai 0.08 Volt dan nilai resistansi sensor sebesar 180 KΩ. Pada peningkatan konsentrasi gas menyebabkan peningkatan tegangan output sensor dan sebaliknya terjadi penurunan pada nilai resistansi